Nanotechnology in medicine and healthcare: Possibilities progress and problems - Jillian Gardner (South African Journal of Bioethics and Law, 2015)
Nanotechnology or nanoscience covers the investigation, design, manipulation, precision placement, measurement, modelling or fabrication of matter, structures, devices and systems that exist at the nanoscale â€“ essentially at the atomic and molecular size levels. Nanotechnology has the potential to change the way we address some of the world's most critical development problems. In 2005, the United Nations (UN) Millennium Projectâ€™s Taskforce on Science, Technology and Innovation concluded that nanotechnology can contribute to the attainment of the Millennium Development Goals (MDGs), specifically, the goals to reduce child mortality, improve maternal mortality and combat HIV/AIDS, malaria and other diseases. Health, specifically improved primary healthcare, is one of six focus areas highlighted in South Africaâ€™s National Nanotechnology Strategy (NNS), where nanotechnology can offer the most significant benefits for the country. Nanotechnology can revolutionise the practice of medicine and the delivery and accessibility of health care. However, despite the significant benefits of nanotechnology, there are problems that could prevent it from being widely accepted. The qualities that make nanotechnology so appealing are also those that give rise for concern. In particular, there are uncertainties about its potential impact on human health, the environment and societies in general, along with the concern that nanotechnology, much like genetic engineering or modification, is â€œmessingâ€ with the building blocks of nature and is therefore â€œunnaturalâ€ even unethical. This article considers these concerns and concludes that there is nothing intrinsically good or bad about nanotechnology, but that its acceptability will depend largely on how it used and introduced into society.Â